PEMBELAJARAN KOOPERATIF (COOPERATIVE LEARNING) DALAM PENGAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMP NEGERI 9 SATAP WERA - Adawiyah, Rabiatun; Ahmadin; Ferdiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Cooperative learning is an educational method that emphasizes cooperation among students to achieve common learning goals. This research aims to explore the application of cooperative learning in teaching Islamic Religious Education at SMP Negeri 9 Satap Wera. The method used was descriptive qualitative approach, with data collection through interviews and observations of teachers and students. The results showed that the application of cooperative learning is very effective in increasing students' participation, improving material understanding, and developing social skills. Students felt more confident and active in discussions, while teachers noted an increase in classroom interaction. The implication of this study shows that cooperative learning can be a useful strategy in education, especially in subjects that require social interaction. This research also provides novelty by filling a gap in the literature regarding the application of cooperative learning in the context of Islamic Religious Education, as well as highlighting the challenges faced by teachers in its implementation.